Acetic Acid Mediated for One-Pot Synthesis of Novel Pyrazolyl s-Triazine Derivatives for the Targeted Therapy of Triple-Negative Breast Tumor Cells (MDA-MB-231) via EGFR/PI3K/AKT/mTOR Signaling Cascades - Ihab Shawish; Assem Barakat; Ali Aldalbahi; Walhan Alshaer; Fadwa Daoud; Dana A. Alqudah; Mazhar Al Zoubi; Ma’mon M. Hatmal; Mohamed S. Nafie; Matti Haukka; Anamika Sharma; Beatriz G. de la Torre; et al. (Pharmaceutics, 2022)
Here, we described the synthesis of novel pyrazole-s-triazine derivatives via an easy one-pot procedure for the reaction of β-dicarbonyl compounds (ethylacetoacetate, 5,5-dimethyl-1,3-cyclohexadione or 1,3-cyclohexadionone) with N,N-dimethylformamide dimethylacetal, followed by addition of 2-hydrazinyl-4,6-disubstituted-s-triazine either in ethanol-acetic acid or neat acetic acid to afford a novel pyrazole and pyrazole-fused cycloalkanone systems. The synthetic protocol proved to be efficient, with a shorter reaction time and high chemical yield with broad substrates. The new pyrazolyl-s-triazine derivatives were tested against the following cell lines: MCF-7 (breast cancer); MDA-MB-231 (triple-negative breast cancer); U-87 MG (glioblastoma); A549 (non-small cell lung cancer); PANC-1 (pancreatic cancer); and human dermal fibroblasts (HDFs). The cell viability assay revealed that most of the s-triazine compounds induced cytotoxicity in all the cell lines tested. However, compounds 7d, 7f and 7c, which all have a piperidine or morpholine moiety with one aniline ring or two aniline rings in their structures, were the most effective. Compounds 7f and 7d showed potent EGFR inhibitory activity with IC50 values of 59.24 and 70.3 nM, respectively, compared to Tamoxifen (IC50 value of 69.1 nM). Compound 7c exhibited moderate activity, with IC50 values of 81.6 nM. Interestingly, hybrids 7d and 7f exerted remarkable PI3K/AKT/mTOR inhibitory activity with 0.66/0.82/0.80 and 0.35/0.56/0.66-fold, respectively, by inhibiting their concentrations to 4.39, 37.3, and 69.3 ng/mL in the 7d-treatment, and to 2.39, 25.34 and 57.6 ng/mL in the 7f-treatment compared to the untreated control.